1993
DOI: 10.1095/biolreprod48.4.729
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Porcine Endometrial Development Involves Coordinated Changes in DNA Synthesis, Glycosaminoglycan Distribution, and 3H-Glucosamine Labeling1

Abstract: To determine whether neonatal porcine endometrial development involved alterations in endometrial DNA synthesis, glycosaminoglycan (GAG) distribution, and/or 3H-glucosamine labeling, gilts were assigned randomly at birth (Day 0) to be hysterectomized on either Day 0, 7, 14, 28, 42, or 56. Uteri were processed for histology and Alcian blue-8GX (AB) histochemistry or cultured as explants in the presence of [methyl-3H]thymidine (3H-Thd) or D-[6-3H]glucosamine (3H-GlcN) and processed for subsequent autoradiography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 44 publications
4
20
0
Order By: Relevance
“…Consistent with earlier observations [35,37,44,45], differentiation of GE from LE, apparent on PND 2, as well as proliferation and development of nascent uterine glands was marked by intense, tissue site-specific PCNA and ESR1 immunostaining in GE that became more pronounced by PND 14. Patterns of cell proliferation reflected by PCNA immunostaining observed here were similar to those described for nascent uterine GE in the neonatal pig [35,45], sheep [46], and mouse [47,48].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with earlier observations [35,37,44,45], differentiation of GE from LE, apparent on PND 2, as well as proliferation and development of nascent uterine glands was marked by intense, tissue site-specific PCNA and ESR1 immunostaining in GE that became more pronounced by PND 14. Patterns of cell proliferation reflected by PCNA immunostaining observed here were similar to those described for nascent uterine GE in the neonatal pig [35,45], sheep [46], and mouse [47,48].…”
Section: Discussionsupporting
confidence: 91%
“…Transient ERa activation in neonatal gilts, induced by administration of estrogen for 14 days from birth, altered endometrial function and compromised uterine capacity for conceptus support in adults (Tarleton et al 2003). Uterine responses to estrogen in neonatal gilts were exposure period-specific and related directly to endometrial ER architecture characteristic of the period during which exposure occurred (Spencer et al 1993, Tarleton et al 2001. Collectively, data indicate that ER-dependent developmental events characteristic of the period from birth through PND 14 are critical determinants of porcine uterine capacity.…”
Section: Introductionmentioning
confidence: 85%
“…Alternatively, EGF and IGF might act as estrogen-dependent mediators of estrogen action in the presence of the ovary and adrenal but independently of estrogen in their absence (i.e., a compensatory mechanism). Spencer et al showed that in the pig, postnatal uterine gland differentiation is accompanied by an increased glandular epithelial cell DNA labeling index and a specific pattern of glycosaminoglycan distribution [2]. Those outcomes, observed during the ovary-independent period of uterine differentiation, led the investigators to conclude that morphogenesis is regulated within the immediate environment of the epithelial cells.…”
Section: Discussionmentioning
confidence: 99%